Pengaruh FDR, NPF, BOPO terhadap Roa dan Bi Rate terhadap NPF Perbankan Syariah - Septiani, Maulita; Aziz, Abdul (An Nuqud Journal of Islamic Economics, 2024)
Return On Assets is one of the assessment indicators used to measure the profitability of Islamic banks. There are several factors that can influence ROA in the form of internal factors such as FDR, NPF and BOPO as well as external factors such as the BI Rate. This research aims to analyze the influence of Internal Factors (FDR, NPF, BOPO) on ROA and analyze the influence of External Factors (BI Rate) on NPF. This research is quantitative descriptive research conducted at PT. Bank Jabar Banten Syariah by taking data on financial data that has been published in 2011-2020 on a quarterly basis. Based on the results of this research, it states that in the first model, partially and in the short term, the FDR and BOPO variables do not have a significant influence on ROA, while the NPF variable has a negative and significant influence on ROA. In the second model the BI Rate has a negative and significant influence on NPF. Apart from that, the research results simultaneously state that there is a significant influence on ROA in model one (FDR, NPF, and BOPO). In the analysis of the coefficient of determination (R2), the variables FDR, NPF and BOPO have an influence on ROA of 79.74%, and the remaining 20.26% is influenced by other variables not included in the research